PENEGAKAN HUKUM TERHADAP PENGGUNAAN SENJATA API RAKITAN DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Yosua Novfryan Nainggolan; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Assembled firearms are also called small arms because they are replicas and are assembled followingthe patterns of standard combat firearms, which are produced by illegal